PENDIDIKAN AGAMA DAN MORAL DALAM PERSPEKTIF GLOBAL - Nova Yanti (STAI Hubbulwathan Duri, 2016)
Decreasing moral values today is very worrying. It does not only happen in adults, but also occurs in youth and students. The factor that causes the wrong attitude in teenagers is looseness of grip on religion values. Moreover, the moral guidance ineffective in homes, schools, and communities also cause the wrong attitude in teenagers. Cultural materialistic, hedonistic, secularism and lack of awareness of government also joined the cause of the decline in moral values today. To solve these issues, religion education should be enhanced by involving members of the household, school, and community.